Putative receptor binding sites on alphaviruses as visualized by cryoelectron microscopy. - Smith, T J (1995)
The structures of Sindbis virus and Ross River virus complexed with Fab fragments from monoclonal antibodies have been determined from cryoelectron micrographs. Both antibodies chosen for this study bind to regions of the virions that have been implicated in cell-receptor recognition and recognize epitopes on the E2 glycoprotein. The two structures show that the Fab fragments bind to the outermost tip of the trimeric envelope spike protein. Hence, the same region of both the Sindbis virus and Ross River virus envelope spike is composed of E2 and is involved in recognition of the cellular receptor.